The Recurrent Vulvovaginal Candidiasis: Proposal of a Personalized Therapeutic Protocol. (9th August 2011) - Murina, F.; Graziottin, A.; Felice, R.; Radici, G. L.; Di Francesco, S.
Abstract : Background . Recurrent vulvovaginal candidiasis (RVC) is an increasing challenge in clinical practice. Objective . The purpose of this study was to reduce the episodes of RVC through the intake of fluconazole 200 mg/dose with a personalized regimen at growing administration intervals with a probiotic. Method . 55 patients received a 200 mg fluconazole as an induction dose for 3 alternate days. Symptoms resolution after 10–14 days made the patients eligible to continue with a maintenance therapy of fluconazole weekly for one month, followed by 200 mg after 10, 15, 20 and 30 days. Patients were allowed to move on to the next level of maintenance therapy only if they were symptom free. Patients were also given a probiotic with Beta Glucan and Echinacea Purpurea. Results . Among the 55 patients enrolled, four (7%) have withdrawn after the induction phase. 51 patients completed the whole therapeutic maintenance period, and eight (15, 6%) experienced a recurrence before the end of the therapy. Five women (9, 8%) relapsed (two after 2 months and three after 6 months). Conclusion . The positive results of our study prove the effectiveness of an individualized protocol for a rather short period, with a slowly decreasing administration of fluconazole + probiotic.